Neotropical Blepolenis butterflies: wing pattern elements, phylogeny, and Pleistocene diversification (Lepidoptera, Nymphalidae) - Penz, Carla M.; Mohammadi, Neda; Wahlberg, Niklas (Zootaxa, 2011)
This study re-describes and provides a phylogeny for the Brassolini genus Blepolenis, which includes three species from the Brazilian Atlantic forest. A diagnosis and illustrations of habitus and genitalia are given for each species. We compare variation in wing color pattern among the genera Blepolenis, Opsiphanes, Orobrassolis and Mielkella, and discuss the repeated loss of male wing androconial organs within Blepolenis. DNA sequence (nuclear and mitochondrial genes) provided the strongest signal for phylogeny reconstruction, given that Blepolenis species are morphologically homogeneous. Estimated time of divergence between Blepolenis and Opsiphanes dates from the Mid Miocene (ca. 15 million years ago), and was followed by an apparent period of stasis. Extant Blepolenis species seem to have diverged in the Pleistocene (ca. 2.5 mya).